2010
DOI: 10.1097/dbp.0b013e3181d5a4e2
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Functioning in Children With FAS, pFAS, and ARND

Abstract: The children who met tightly defined physical criteria for a diagnosis of FAS demonstrated significantly poorer neurodevelopmental functioning than children with pFAS and ARND. Children in these latter 2 groups were similar in all neurodevelopmental domains that were tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 18 publications
4
50
0
Order By: Relevance
“…2,17,18 Recent studies have documented that use of third percentile for growth assessment neurodevelopmentally differentiates children within the fetal alcohol spectrum. 10,15 Also, growth criteria below third percentile align more closely with the original definition of FAS. 1 • Facial dysmorphology: abnormal measurements of the upper lip (rank 4 or 5) and the philtrum (rank 4 or 5) and shortened palpebral fissures based on direct measurement or, after 2003, according to analysis of facial features utilizing the Lip-Philtrum Guide and digital facial photograph based on the criteria of Astley and Clarren.…”
Section: Diagnostic Assignmentmentioning
confidence: 88%
See 1 more Smart Citation
“…2,17,18 Recent studies have documented that use of third percentile for growth assessment neurodevelopmentally differentiates children within the fetal alcohol spectrum. 10,15 Also, growth criteria below third percentile align more closely with the original definition of FAS. 1 • Facial dysmorphology: abnormal measurements of the upper lip (rank 4 or 5) and the philtrum (rank 4 or 5) and shortened palpebral fissures based on direct measurement or, after 2003, according to analysis of facial features utilizing the Lip-Philtrum Guide and digital facial photograph based on the criteria of Astley and Clarren.…”
Section: Diagnostic Assignmentmentioning
confidence: 88%
“…Previous studies have demonstrated that anywhere from 40% to 75% of children with FASD are diagnosed with ADHD. 15,26,27 However, there are qualitative differences in the types of attention problems seen in children with FASD as compared with children with ADHD. [28][29][30] Children with ADHD and FASD have been shown to have greater deficits in verbal comprehension and perceptual reasoning than children having ADHD without prenatal alcohol exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The most severe and common impairments in intellectual functioning (IQ<70) are seen for FAS (Pulsifer 1996); those with FAS tend to have lower IQ compared to those with pFAS or ARND (Chasnoff et al 2010). IQ is arguably the characteristic most strongly associated with EF in FASD populations (Pulsifer 1996;Steinhausen and Spohr 1998).…”
Section: Factors That Influence the Association Between Fasd And Efmentioning
confidence: 97%
“…In the largest profile study conducted to date Astley (2010) found a linear trend of functioning, such that those diagnosed with neurodevelopmental disorder/alcoholexposed (ND/AE) showed the best performance, followed by the static encephalopathy/alcohol-exposed (SE/AE) group, with the most pronounced deficits observed in the FAS/pFAS group. Chasnoff et al (2010) also found that children with FAS were significantly more impaired on measures of intelligence, executive functioning, and memory compared with those with pFAS and ARND. Similarly, Nash et al (2013) found that children with FASD were more impaired on tasks evaluating verbal reasoning, memory, language, and mathematics relative to children with PAE who did not receive an FASD diagnosis.…”
Section: Carmen Rasmussenmentioning
confidence: 77%
“…Alternatively, Astley's (2010) large scale cohort in Washington found a linear trend differentiating cognitive functioning among individuals with ND/AE, SE/AE, and FAS/pFAS, and Chasnoff et al (2010) similarly found differences in functioning between children with FAS compared with those with pFAS and ARND. Different diagnostic approaches and classifications may impact Table 3 under main effects for group b Mean difference scores vary for within FASD group comparisons as the mean for QC includes only the same number of participants who completed both QC and the subtest against which QC is being compared (not all participants completed all subtests of each measure) c Meets Benjamini-Hochberg (1995 false discovery rate criterion the interpretation of within-FASD comparisons in cognitive functioning, underscoring the need for further research in this area across methodologies and diagnostic classification systems.…”
Section: Discussionmentioning
confidence: 99%